2021
DOI: 10.1161/circulationaha.120.051877
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Endothelial Cell S -Sulfhydrome Highlights the Crucial Role of Integrin Sulfhydration in Vascular Function

Abstract: Background: In vascular endothelial cells, cysteine metabolism by the cystathionine γ lyase (CSE), generates hydrogen sulfide-related sulfane sulfur compounds (H 2 S n ), that exert their biological actions via cysteine S -sulfhydration of target proteins. This study set out to map the " S -sulfhydrome" i.e. the spectrum of proteins targeted by H 2 S n in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 71 publications
2
59
0
Order By: Relevance
“… 55 Several high throughput studies of post-translational modification of protein cysteinyl thiols (-SH) to persulfides (-SSH) demonstrated that cysteine residues in α- and β-tubulin are persulfidated in response to H 2 S donors in various cell types. 56 , 57 Given the prominent role of cytoskeleton dynamics and remodelling during mitosis and cell migration, we propose that STS/H 2 S-driven microtubule depolymerisation, secondary to cysteine persulfidation, contributes to cell cycle arrest and reduces migration in VSMC.…”
Section: Discussionmentioning
confidence: 97%
“… 55 Several high throughput studies of post-translational modification of protein cysteinyl thiols (-SH) to persulfides (-SSH) demonstrated that cysteine residues in α- and β-tubulin are persulfidated in response to H 2 S donors in various cell types. 56 , 57 Given the prominent role of cytoskeleton dynamics and remodelling during mitosis and cell migration, we propose that STS/H 2 S-driven microtubule depolymerisation, secondary to cysteine persulfidation, contributes to cell cycle arrest and reduces migration in VSMC.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, thiol™disulfide exchanges in intrachain disulfide bonds have been proposed to play a key role in microtubule assembly (42). Several high throughput studies of post-translational modification of protein cysteinyl thiols (-SH) to persulfides (-SSH) demonstrated that cysteine residues in α- and β-tubulin are persulfidated in response to H 2 S donors in various cell types (43, 44). Given the prominent role of cytoskeleton dynamics and remodelling during mitosis and cell migration, we propose that STS/H 2 S-driven microtubule depolymerisation, secondary to cysteine persulfidation, contributes to cell cycle arrest and reduces migration in VSMC.…”
Section: Discussionmentioning
confidence: 99%
“…Although targeting TAAs has had some early clinical trials, to date, the vaccines lacked potency because of issues with their central or peripheral tolerance mechanisms 35 . In addition, although TAA analyses using sequencing and MS/MS techniques showed successful identification, the results were not supported by adequate clinical data 41 . Thus, more attention should be directed towards developing tumor-specific and potent therapeutic vaccines to favor effective immune responses.…”
Section: Taasmentioning
confidence: 79%